Men [videorecording (DVD)] - Garland, Alex, 1970-; Buckley, Jessie, 1989-; Kinnear, Rory, 1978-; Rankin, Gayle; Essiedu, Paapa, 1990-; Fuzzface, 1971-; Salisbury, Ben; Hardy, Rob (Cinematographer) (Lionsgate, 2022)
In the aftermath of a personal tragedy, Harper retreats alone to the beautiful English countryside, hoping to find a place to heal. However, someone or something from the surrounding woods appears to be stalking her. What begins as simmering dread soon becomes a fully formed nightmare, inhabited by her darkest memories and fears.